EFL students’ attitudes towards learner autonomy in English vocabulary learning - Thao Quoc Tran (English Language Teaching Educational Journal, 2020)
Whether EFL learners can use English well or not depends much on vocabulary they possess. Learner autonomy (LA), however, plays a pivotal role in amassing EFL learners’ vocabulary. This study endeavored to explore students’ attitudes towards LA in English vocabulary learning. Two hundred English majors from a Ho Chi Minh City based higher institution, Vietnam got involved in answering the closed-ended questionnaire, and ten students took part in semi-structured interviews. The findings indicated that participants were cognitively aware of the importance of LA in English vocabulary learning, but affectively and behaviorally they showed low interest in LA in English vocabulary learning. Such findings may shed light on how to improve the teaching and learning of the English language in general and English vocabulary in particular at the research context and other similar EFL contexts.